Carta de Roberto H. Todd a Antonio R. Barceló - Todd, Roberto H.; Barceló, Roberto H. (My University, 1931)
Actividad del Asambleísta Gustavo Cruzado Silva en el pleito del Municipio de San Juan.
Keywords: Cruzado Silva, Gustavo; Municipal government--Puerto Rico.; Gobierno Municipal--Puerto Rico.; Partido Unión de Puerto Rico